Clinical stages in patients with primary and subsequent cancers based on the czech cancer registry 1976-2005 - Geryk, Edvard; Stampach, Radim; Dítě, Petr; Kozel, Jiří; Horváth, Teodor; Kubíček, Petr (ISRN oncology, 2013)
Of 1,486,984 new cancers registered in the Czech Cancer Registry in 1976-2005, 290,312 (19.5%) were multiple malignant neoplasms (MMNs), of which there were 65,292 primary and 89,796 subsequent cases in men and 59,970 primary and 75,254 subsequent cases in women. The duplicities were higher in women, and the triplicities and others (3-6 MMNs) were higher in men. The most frequent diagnoses were the primary cancers of skin, gastrointestinal and urinary tract, male genital organs, respiratory tract in men, and cancers of skin, breast, female genital organs, and gastrointestinal tract in women. The analysis of the early and advanced clinical stages shows that the number of subsequent advanced stages increased after primary advanced stages. Their time-age-space distributions visualized maps of MMNs in 14 Czech regions. These results support the improvement of algorithms of dispensary care for the early detection of the subsequent neoplasms.